The Effect of Probiotic Starter Culture Variation on the Quality of Yogurt Based on Indonesian National Standard - Ih, Hariyanto; Cristin, Bella; Nurbaeti, Siti Nani (Biology, Medicine, & Natural Product Chemistry, 2024)
Yogurt is usually made by two lactic acid bacteria such as Streptococcus thermophilus and Lactobacillus bulgaricus. However, three to seven lactic acid bacteria are also used in several products. Therefore, this study aimed to examine the effect of variations in the number of starter bacteria and compare to Indonesian National Standard (SNI). The experimental method was used with starter variations, including a combination of two (Lactobacillus bulgaricus and Streptococcus thermophilus); three (Lactobacillus bulgaricus, Streptococcus thermophilus, Lactobacillus acidophilus); and seven bacteria (Lactobacillus bulgaricus, Streptococcus thermophilus, Lactobacillus acidophilus, Lactobacillus casei, Lactobacillus rhamnosus, Bifidobacterium longum, and Bifidobacterium infantis). The results showed that the yogurt with two and seven bacteria was within the range of SNI value standard. The pH, viscosity, syneresis, lactic acid content, total protein, and total number of bacteria for yogurt with two bacteria were 3.92, 453.76 cP, 88.05%, 1.27%, 3.26%, and 2.47 x 1012 Cfu/mL, respectively. The values for yogurt with seven bacteria were 4.11, 478.23 cP, 97,45%, 0,98%, 2.7%, and 1.53 x 1010, respectively, while formulas with three bacteria did not reach the pH standard. However, the atypical taste was given by the seven starter bacteria and the use of various bacteria starters affected the quality of yogurt. Specifically, formulas composed of two bacteria showed the best results according to SNI.